KONTEKSTUALISASI HADIS PEMINANGAN PEREMPUAN TERHADAP LAKI-LAKI - Masduki, Masduki (UIN Sunan Kalijaga Yogyakarta, 2019)
This article is talking about the contextual understanding of Hadith about women proposing toward men and how this phenomenon develops in the contemporary era. Islam requires that a proposing is done before marriage. The practice of proposing generally is held by men. However, in several locations, it is found that a proposing is committed by women. They are doing it because of their understanding of a hadith which explains that in Islam, a woman has the right to propose a man. On the other side, Islam does not regulate who must propose whether men or women. Even though, there is a hadith which tells that a woman offered her self to be married by a pious man. As an open and changed text, a hadith can be explained by many ways of interpretation. One of them is contextual understanding. Therefore, contextual understanding of woman proposing toward a man which is based on the hadith is allowed because the prophet did not give a legal decision and forbid it.Â Keywords: Hadith, Women Proposing, Contextual Understanding